Role Dynamics in a Structured Relationship: The EU–China Strategic Partnership*. (20th October 2016) - Michalski, Anna; Pan, Zhongqi
Abstract: In this article, we investigate the function of strategic partnerships as a new type of state interaction in the international system. We are primarily interested in the dynamics of strategic partnerships and to that aim we analyze the competitive role‐playing that occurs in the EU–China Strategic Partnership. We contend that EU and China engage in competitive role‐playing in order to enhance their position and status as global actors and to seek recognition of their international roles. The interaction between the EU and China is analyzed throughout four periods in which their role conceptions have undergone change and adaptation. The article claims to make a theoretical contribution by developing the understanding of social interaction in the international system by conceptualizing strategic partnerships as arenas (structures) in which international roles play out, and an empirical contribution by tracing the complexities of the EU–China Strategic Partnership by utilizing role theory's conceptual apparatus.